An?lise te?rica da deflex?o de vigas de concreto com agregados reciclados de RCD - Oliveira, Jos? Jorge Arag?o (2018)
In Brazil, the use in civil construction of recycled aggregates of construction and demolition replacing natural aggregates is only allowed in concrete without structural purposes. National standards of structural civil engineering prevents its adoption as a structural element of reinforced concrete. The scientific knowledge, still incipient, competes for use with restrictions, even in countries where the practice is permitted .. Physical characteristics, such as porosity and heterogeneity significantly differ from natural aggregates, interfering directly in its mechanical properties. It is fundamental to know more deeply these properties for use of the material with guarantee of safety, durability and economy. The present research proposed to evaluate the influence of the replacement of the natural aggregates by RCD aggregates on the immediate deflection of reinforced concrete beams. The theoretical study of deflection was made by adopting the Bilinear method of CEB, it being necessary due adequacy of the formulations physical characteristics and geometry of structural parts used in the experimental results used for further research. We studied the Moment x Deflection behavior for the State Service Limit, comparing it with the experimental results. Thus it was possible to evaluate the effect of the substitution of the natural aggregates by RCD on the performance of the deflection of the beams. It was concluded that for 50% of substitution the effect on deflection is very little altered. For 100% replacement, there is a slightly lower performance, however with values that allow, be considered satisfactory. The results of the analyzes allow to affirm that, in relation to the immediate deflection, it is possible the partial and total replacement of the natural aggregates by RCD